2012
DOI: 10.1039/c2ra20453c
|View full text |Cite
|
Sign up to set email alerts
|

Size controlled synthesis of highly dispersed anatase/rutile nanoparticles with photocatalytic activity toward salicylic acid degradation

Abstract: TiO 2 nanocrystals supported in SBA-15 pores were prepared by a simple route of successive cycles of impregnation of SBA-15 with titanium(IV) di-(n-propoxy)-di-(2-ethylhexanoate) followed by thermal treatment. Anatase and rutile phases were identified by XRD in the materials obtained after cycles 1, 3, 5, 7 and 10. Raman scattering combined with XRD and TEM shows that titania is in a nanometric regime. Increases in the size of the titania nanocrystals, as well as increases in the TiO 2 content in the final mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 35 publications
1
2
0
1
Order By: Relevance
“…There are many efforts to increase the TiO 2 content in the PMSs for controlling the photocatalytic performances. ,,, Landau et al reported a high TiO 2 content (64 mass % TiO 2 ), which was obtained by impregnation repeated twice using the high concentration of tetrabutyl orthotitanate (80 mass %) solution in n -decane . The crystal size of anatase was determined to be 5.5 nm, which was consistent with the BJH pore diameter of the used SBA-15 (6 nm).…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…There are many efforts to increase the TiO 2 content in the PMSs for controlling the photocatalytic performances. ,,, Landau et al reported a high TiO 2 content (64 mass % TiO 2 ), which was obtained by impregnation repeated twice using the high concentration of tetrabutyl orthotitanate (80 mass %) solution in n -decane . The crystal size of anatase was determined to be 5.5 nm, which was consistent with the BJH pore diameter of the used SBA-15 (6 nm).…”
Section: Resultssupporting
confidence: 53%
“…The TiO 2 contents reported so far were not consistent with the decrease of the pore volume, indicating the different contribution of the externally formed anatase and anatase in the mesopore. The higher TiO 2 contents have been achieved by the repeated infiltration; ,,, however, it was difficult to avoid the formation of the anatase particles on the external surface of mesoporous silicas. Here, by using neat TTIP without solvents, the high TiO 2 content (62 mass %) in the hybrid was obtained by a single infiltration step.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No processo de impregnação desenvolvido no trabalho usamos um composto metalorgânico que, a princípio, quando exposto a altas temperaturas em atmosfera oxidante perde a cadeia orgânica, restando apenas o óxido do metal correspondente. No entanto, dada a morfologia cilíndrica da partícula foi possível implementar a impregnação por metalorgânico [112,113] em algo mais elaborado.…”
Section: Impregnação Química E Formação Da Ferrita De Cofe 2 O4unclassified